https://doi.org/10.36873/aev.v1: KARAKTERISTIK KIMIA DAN FISIKA TANAH PMK (PODSOLIK MERAH KUNING) AKIBAT PENGGUNAAN LAHAN YANG BERBEDA, Irwan Surya Aditya * , Fengky Florante Adji, Kamillah - Administrator Journal (Agrienvi: Jurnal Ilmu Pertanian, 2019)
ABSTRACTRed-yellow podzolic soil is widespread in West Kotawaringin and mostly used as agricultural land. It causechanges in soil properties so that soil fertility analysis is needed. The research aims to study the chemistry andphysics of red-yellow podzolic, as a result of agricultural activities. The research was conducted by taking soilsamples from unmanaged land (control land) and oil palm plantations belong to KUD Tani Subur which appliedoil palm integration with cows in Pangkalan Lada, Central Kalimantan. In this study we conducted simple randomsampling method with 5 replications. Variables used as parameter in the study are porosity, bulk density, pH, Ctotal, N-total, P-available, Cation Exchange Capasity (CEC), base saturation (BS), Fe, and Al-exchangeable. Theresults show oil palm plantations have soil porosity 51,84%, bulk density 1,28 g cm-3, pH soil about 5,02-5,04;C-total 1,23-1,69%; N- total%; 0,06-0,11%, P-available 8,1-8,9 ppm; CEC 18,52-22,85 me 100g-1; BS 1,79-3,24; Fe 0,59-0,82 ppm; and Al- exchangeable 110,46-111,29 ppm, but control land have soil porosity 45,03%;bulk density 1,46 g cm-3; pH 5,04-5,13; C-total 0,76-1,05; N-total 0,09-0,19; P- available 9,3-9,7 ppm; CEC20,30-22,27 me 100g-1; BS 2,33-2,76%; Fe 0,02-0,68 ppm; and Al-ec 126,67-156,60 ppm. Land use of RYP soiltypes as oil palm plantations with semi- organic processing techniques does not degrade the soil, and couldincrease land productivity compared to unmanaged land.Keywords: RYP, soil chemistry and physics, different land use.